Breeding practices and selection criteria in Gudali cattle breed from Benin: implications for the design of a community-based breeding program - Zorobouragui, Loukaiya; Houaga, Isidore; Assani, Alassan S.; Worogo, Hilaire S. S.; Kinkpe, Lionel; Periasamy, Kathiravan; Alkoiret, Ibrahim T. (Frontiers in Animal Science, 2025)
Understanding farmers’ breeding systems and preferred traits is crucial for establishing effective genetic improvement programs. This study investigated Gudali cattle breed selection, breeding objectives, and selection criteria in North-east Benin (Malanville and Tchaourou). We surveyed 120 Gudali cattle farmers using a structured questionnaire and conducted hierarchical clustering using R software. We identified the distribution of farmers based on herd composition and production systems. Farmers were grouped into four classes: Sedentary Purebreds (16.67%), Transhumant Purebreds (33.33%), Sedentary Mixed Breeds (34.17%), and Transhumant Mixed Breeds (15.83%), with average Gudali herd sizes ranging from 23.68 to 90.11 heads depending on the system. The overall average herd size was 42.67 ± 6.00 heads. The majority of farmers owned different breeds, including Borgou (26.67%), Yakana (26.67%), and Azawak (7.5%), with only 32.5% having Gudali only herds. Farmers chose Gudali cattle for their milk production, good growth and market value, with 96.67% prioritizing milk production. The main selection criterion was coat color in all breeding systems with respective indices of 0.59; 0.57; 0.54 and 0.47 respectively for sedentary purebred; sedentary mixed breed; transhumant purebred and transhumant mixed breed systems. Most mixed breed farmers (55.84%) cross Gudali with local breeds for better dairy performance. While only 3.33% of farmers were aware of community-based breeding programs (CBBP), there was strong interest (95%) in participating. Potential challenges such as access to feed and disease management were reported. The proposed mitigation strategies include establishing pasture areas and strengthening collaboration among stakeholders. Implementing CBBP programs by incorporating farmers’ preferences and practices, could sustainably improve Gudali cattle productivity and resilience in Benin.